Association between psoriasis and peripheral artery occlusive disease: a population-based retrospective cohort study - Yeh, Chao-Bin; Yeh, Liang-Tsai; Yang, Shun-Fa; Wang, Bo-Yuan; Wang, Yu-Hsun; Chan, Chi-Ho (Frontiers in Cardiovascular Medicine, 2023)
Introduction Psoriasis (PSO) is a chronic skin condition that affects a variety of disorders, especially the cardiovascular system. This study investigated the association between PSO and peripheral arterial disease (PAOD). Methods A retrospective cohort study design was carried out between 2000 and 2018. The exposure subject was a newly diagnosed PSO. The diagnosis of PSO was never elaborated as a comparison subject. Balanced heterogeneity of the two groups was used by propensity score matching. The cumulative incidence of PAOD between the two groups was performed using Kaplan-Meier analysis. The Cox proportional hazard model was used to measure the risk of PAOD risk hazard ratio. Results After matching the 1: 1 propensity score, 15,696 subjects with PSO and the same number of subjects without the diagnosis of PSO were recruited. The PSO subject had a higher risk of PAOD than the non-PSO subject (adjusted HR = 1.25; 95% CI = 1.03-1.50). In the 40-64-year-old subgroup, the subject of PSO exhibited an increased risk of PAOD than the subject without PSO. Conclusion Psoriasis is associated with an increased risk of peripheral arterial disease and curative care is necessary to reduce the risk of PAOD..